1994
DOI: 10.1093/oxfordjournals.aje.a117051
|View full text |Cite
|
Sign up to set email alerts
|

Decision Latitude, Psychologic Demand, Job Strain, and Coronary Heart Disease in the Western Electric Study

Abstract: The hypothesis that low decision latitude and high psychologic demand are associated with an increased risk of the incidence of and mortality from coronary heart disease was investigated in a 25-year follow-up study of 1,683 men aged 38-56 years who participated in the Chicago Western Electric Study (1957-1983). Scores for decision latitude and psychologic demand, which had been linked to the 1960 US Census occupation codes, were assigned to men in the Western Electric cohort based on job title at the initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
1
3

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(113 citation statements)
references
References 0 publications
7
102
1
3
Order By: Relevance
“…All of these studies reported a positive association between work stress and CHD that was robust to adjustment for other risk factors. The number of identified independent prospective cohort studies assessing the job-strain model was 11, relating to a 7-10 times greater total population than that for the other work-stress models (37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Although the overall summary estimate of the age-and gender-adjusted relative risk for CHD among employees with job strain suggested increased risk, some single studies reported null findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these studies reported a positive association between work stress and CHD that was robust to adjustment for other risk factors. The number of identified independent prospective cohort studies assessing the job-strain model was 11, relating to a 7-10 times greater total population than that for the other work-stress models (37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Although the overall summary estimate of the age-and gender-adjusted relative risk for CHD among employees with job strain suggested increased risk, some single studies reported null findings.…”
Section: Discussionmentioning
confidence: 99%
“…Typically the studies assessed work stress at one point in time only. Eleven independent studies tested the job-strain model (37)(38)(39)(40)(41)(42)(43)(44)(45)(46). While the measure of job strain in all of these studies was generated by cross-tabulating the dichotomized or trichotomized scales of job demands and job control, the items included in these scales varied between the studies.…”
Section: Assessment Of Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…The full model has been confirmed in a minority of studies only (23)(24)(25)(26). Single components have only partially been found to be significantly related to smoking status (27)(28)(29)(30)(31)(32)(33) and, if so, more often among women than among men. Eight studies did not report any association between model components and smoking status (34)(35)(36)(37)(38)(39)(40)(41).…”
Section: The Challenge Of Mechanisms: Health Risk Behaviormentioning
confidence: 90%
“…This meaning is clearly evident in Karasek's (1979) Longitudinal data would be more useful for examining causal hypotheses. Ideally, data on the predictor variables would be collected prospectively, and then symptom data would be collected years later, as has been done in a few of the major tests of the job demands-control model (e.g., Alterman, Shekelle, Vernon, & Burau, 1994). Finally, additional cardiovascular outcomes, such as heart disease and arterial disorder, should be ex-amined.…”
Section: Discussionmentioning
confidence: 99%